Víctor Andrés Belaunde and the intellectual debate on the Peruvian reality - Cubas Ramacciotti, Ricardo (Mercurio Peruano, 2016)
Belaunde was, since his youth, a severe critic of the national disorders; he was above all a believer in what Basadre later called the "promise of Peruvian life", ie, "an ideal of individual and collective improvement" to be obtained by the integral development of the country; "the exploitation of its riches, the defense and increase of its population, the creation of a minimum of welfare for every citizen and opportunity for them". The promise implied for Belaunde the formation of a space with an identity and a common tradicion that does not exclude, but integrate the various local cultures.